Transfer accuracy of two indirect bonding techniques—an in vitro study with 3D scanned models. (19th February 2018) - Schmid, Johanna; Brenner, Daniel; Recheis, Wolfgang; Hofer-Picout, Philipp; Brenner, Martin; Crismani, Adriano G
Summary: Background and objectives: Indirect bonding (IDB) proved to be an effective method for appropriate bracket positioning in patients. Different methods and materials are available for fabricating transfer trays. This in vitro study was designed to measure and compare the transfer accuracy of two common IDB methods. Materials and methods: Sixty stone models were fabricated and separated in two groups of 30 models each (15 working models, 15 patient models). After placing brackets on the working models, 30 IDB trays were made: 15 silicone (method I) and 15 double-vacuum forms (method II). With these trays, the brackets were transferred to the patient models. The bracket positions were scanned before and after the IDB procedure with an intraoral scanner. The linear and angular discrepancies were then determined digitally by measuring six different dimensions: occluso-cervical, mesio-distal, bucco-lingual, tip, rotation, and torque. Results: The silicone trays showed fewer transfer discrepancies, on average, in all measured dimensions. There were significant differences between the methods in the occluso-cervical ( P < 0.001), mesio-distal ( P = 0.001), and torque ( P = 0.044) dimensions. With both methods, 100 per cent of the horizontal and transversal measurements of both methods were within the clinically acceptable range of 0.25 mm. With method I, 98.5 per cent of the vertical and 95.9 per cent of the angular measurements were within the range of 0.25 mm and 1°, respectively. With method II, 94 per cent of the vertical and 84.8 per cent of the angular measurements were within the clinically acceptable range. Conclusions: Although both transfer methods showed a high precision, silicone trays scored better in terms of accuracy than double-vacuum forms.